2001
DOI: 10.1097/00005344-200103000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, a Polyphenol Found in Wine, Reduces Ischemia Reperfusion Injury in Rat Kidneys

Abstract: Reactive oxygen species have been implicated in the pathophysiology of renal ischemia reperfusion injury. Antioxidants including polyphenolics have been found to protect renal cells from the cellular injury induced by ischemia and reperfusion. Resveratrol, a stilbene polyphenol found in grapes and red wine, has recently been found to protect isolated rat heart from ischemia reperfusion injury. This study was sought to determine if resveratrol could also protect renal cells from ischemic injury. Male Wistar rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
79
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 20 publications
12
79
1
Order By: Relevance
“…Resveratrol has been shown to restore kidney function in I/R injury in animal experiments (Giovannini et al 2001;Saito et al 2005), although our study on mice failed to demonstrate a protective effect. Giovannini et al (2001) blocked rat renal arteries for 40 minutes and administered resveratrol at 0.23 μ g/kg, while Saito et al (2005) blocked rat renal arteries for 60 min and administered resveratrol at 4 mg/kg.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Resveratrol has been shown to restore kidney function in I/R injury in animal experiments (Giovannini et al 2001;Saito et al 2005), although our study on mice failed to demonstrate a protective effect. Giovannini et al (2001) blocked rat renal arteries for 40 minutes and administered resveratrol at 0.23 μ g/kg, while Saito et al (2005) blocked rat renal arteries for 60 min and administered resveratrol at 4 mg/kg.…”
Section: Discussioncontrasting
confidence: 76%
“…Giovannini et al (2001) blocked rat renal arteries for 40 minutes and administered resveratrol at 0.23 μ g/kg, while Saito et al (2005) blocked rat renal arteries for 60 min and administered resveratrol at 4 mg/kg. They both found decreased serum creatinine levels by resveratrol compared with the vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt1, a mammalian homologue of Sir2, acts on several nuclear proteins, including p53 (2) and forkhead family proteins (FoxOs) (3), and prevents apoptosis. Calorie restriction or resveratrol, which activates Sirt1, is reported to protect from reactive oxygen species (ROS)-induced 2 organ insult (4,5). Additionally, the overexpression of Sirt1 itself also strengthens the stress resistance.…”
mentioning
confidence: 99%
“…Antioxidants have been found to protect renal cells from cellular injury induced by I/R. [22][23][24] The finding of the anti-oxidant effect of hydrogen and its therapeutic value led us to suggest that endogenous hydrogen may play an important physiological role in maintaining homeostasis. Several studies have shown that hydrogen exerts cytoprotective effects after various types of injuries.…”
Section: Discussionmentioning
confidence: 99%